Per una storia dei gruppi subalterni. Considerazioni sul Quaderno 25 - Casalino, Marco (International Gramsci Journal, 2023)
This contribution seeks to deepen the study of the concept of the subordinate group in Gramsci’s thought starting from a reading of the monographic Notebook 25. Within Gramsci’s prison reflection, the lemma “subaltern” takes on a quite significant role, especially in relation to the concept of hegemony. Indeed, we find this concept at the basis of his reflections regarding the study of the nature and formation of the two classes that directly undergo the hegemonic action of the ruling class: the peasants and the workers. The investigation regarding the concept of subaltern also allows a broadening of the discussion beyond the monographic Notebook 25, devoted to it, to create links with those paragraphs of Notebooks 13, 19 and 27 on the subject of Machiavelli and politics, of the Risorgimento and of folklore, all of use in studying the formation of these groups. On the political action of the subalterns, reference is obligatory to the preprison essay Some Aspects of the Southern Question, where with clarity and a certain insistence there emerges the need to politically organize the worker-peasant bloc in order to establish a new communist hegemony.